IMPLEMENTATION OF RISK MANAGEMENT IN DETECTING FINANCIAL FRAUD AT PT WIN WAHANA CIPTAMARGA (AN ISLAMIC ECONOMICS PERSPECTIVE) - kaharuddin kaharuddin; Rika Dwi Ayu Partmitasari; Irwan Misbach (Ad Deenar: Jurnal Ekonomi dan Bisnis Islam, 2026)
In recent years, numerous fraud cases have occurred in the construction sector, not only globally, as reported by ACFE in its 2024 “Report to the Nations,” but also domestically, as is frequently observed. Based on this phenomenon, the researcher is interested in examining how fraud can be detected in construction companies. The object of this study is PT Win Wahana Ciptamarga, a large-scale construction company. The purpose of this research is to investigate the implementation of risk management in detecting financial fraud in the company. The researcher employed interviews with several employees related to the research object and also conducted observation and documentation. The findings indicate that PT Win Wahana Ciptamarga applies the Fraud Risk Management Principles issued by the ACFE (Association of Certified Fraud Examiners). PT Win Wahana Ciptamarga uses an internally developed application named ESAP (Elektronik Sistem Akuntansi Perusahaan/Electronic Corporate Accounting System) to detect transactions with potential fraud. Wahana Ciptamarga employs technology such as ESAP to detect fraudulent activities.